Impact of economic growth on regional development in Jambi Province - Muhammad Iqbal; Muhammad Firdaus; Bambang Juanda; Dedi Budiman Hakim (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
This research work aims to, firstly, analyze the structure of economic growth based on regency/city typology in Jambi Province in 2008-2007, and secondly, to analyze regional development inequality in Jambi Province in 2008-2017. The analytical methods used are cluster analysis and Williamson Index. In this study, regions are grouped based on similar characteristics of economic growth in Regency/City in Jambi Province using cluster analysis in the period 2008 to 2007. The results of the cluster analysis generated three regional groups with different economic characteristics each year. Through Williamson Index it is found that the average value of development inequality in Jambi Province in 2008-2017 is 0.389, indicating that Jambi Province’s inequality index is in the intermediate level. The results of panel data regression analysis show that HDI and Expenditure on Goods and Services have a significant effect on economic growth.